A Facile Approach to Benzosultam‐fused 4‐Imidazolidinone Derivatives from N‐Sulfonyl Ketimine and α‐Halogenated Hydroxamates. Issue 4 (24th January 2022) - Lan, Wenjie; Lei, Rong‐chao; Luo, Jiayu; Qin, Zhaohai; Fu, Bin; Xie, Lei
Abstract: The novel benzosultam‐fused 4‐imidazolidinone scaffold was constructed by a concise [3+2] annulation reaction of α‐halogenated hydroxamates and N‐sulfonyl ketimine for the first time. The transformation proceeded smoothly under mild and transition‐metal‐free conditions in moderate to excellent yields (up to 95 %). Moreover the annulation products are potentially useful and promising for medicinal research. Abstract : A novel and concise [3+2] annulation reaction of α‐halogenated hydroxamates and N‐sulfonyl ketimine to give benzosultam‐fused 4‐imidazolidinone derivatives has been developed under mild and transition‐metal‐free conditions.